Future of mobile Internet : effective targeting in Singapore - Lai, Kareen Siow Hui (2008)
This paper explores the attitude of young Singaporeans, age between 11 to 25 years old, towards Mobile Services. It examines young users’ attitudes toward Internet connection via mobile phone. Respondents are also analyzed according to their online activities and segmented for possible business marketing.